2022
DOI: 10.3390/ijerph19127439
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Population Density and COVID-19 Cases during the Third Wave in Malaysia: Effect of the Delta Variant

Abstract: In this study, we describe the incidence and distribution of COVID-19 cases in Malaysia at district level and determine their correlation with absolute population and population density, before and during the period that the Delta variant was dominant in Malaysia. Methods: Data on the number of locally transmitted COVID-19 cases in each of the 145 districts in Malaysia, between 20 September 2020 and 19 September 2021, were manually extracted from official reports. The cumulative number of COVID-19 cases, popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
5
20
1
1
Order By: Relevance
“…The inclusion of these two sub-districts into the cold spots category could indicate a low level of transmission of Covid-19. This is in line with the results of several studies which found a relationship between population density and the incidence rate of Covid-19 cases in an area (Ganasegeran et al, 2021;Kadi & Khelfaoui, 2020;Md Iderus et al, 2022b;Yin et al, 2021).…”
Section: Covid-19 Distribution Thematic Mapsupporting
confidence: 92%
“…The inclusion of these two sub-districts into the cold spots category could indicate a low level of transmission of Covid-19. This is in line with the results of several studies which found a relationship between population density and the incidence rate of Covid-19 cases in an area (Ganasegeran et al, 2021;Kadi & Khelfaoui, 2020;Md Iderus et al, 2022b;Yin et al, 2021).…”
Section: Covid-19 Distribution Thematic Mapsupporting
confidence: 92%
“…Uncontrolled population growth not only creates food insecurity but also threatens health safety. High population density appears to be associated with cancers, cardiovascular and respiratory diseases (Carnegie et al, 2022); a higher risk of transmission of COVID-19, especially with the Delta variant (Iderus et al, 2022;Jamal et al, 2022); poor living conditions, such as insufficient access to healthy food, drinking water, poverty-related diseases with poor healthcare access. Also, food vulnerability and price volatility are an explosive combination for certain types of conflicts (Gutiérrez-Romero, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Uncontrolled population growth not only creates food insecurity but also threatens health safety. High population density appears to be associated with cancers, cardiovascular and respiratory diseases (Carnegie et al, 2022); a higher risk of transmission of COVID-19, especially with the Delta variant (Jamal et al, 2022;Md Iderus et al, 2022); poor living conditions, such as insufficient access to healthy food, drinking water, poverty-related diseases with poor healthcare access. Also, food vulnerability and price volatility are an explosive combination for certain types of conflicts (Gutiérrez-Romero, 2022).…”
Section: (A) Poor Food Handling and A Lack Of Population Control Thre...mentioning
confidence: 99%